1998
DOI: 10.1017/s1461145798001072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of central serotonergic function in affective and related disorders by the fenfluramine challenge test: a critical review

Abstract: Plasma prolactin levels following oral administration of the serotonin (5-HT) releasing agent, fenfluramine hydrochloride, have been extensively used to evaluate central serotonergic function in affective and related disorders. Cortisol responses to fenfluramine have generally been a less informative measure. In healthy subjects, prolactin release by fenfluramine is dose-dependent, blocked by antagonists of serotonin receptors of the 5-HT-2a/2c type, negatively correlated with age and increased in young female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 0 publications
2
47
0
1
Order By: Relevance
“…[337][338][339] Administration of D-fenfluramine results in a dosedependent rise in prolactin levels, 340 which has been used as an index of central 5-HT responsivity. [341][342][343] The prolactin response to fenfluramine in depression has been studied extensively, with mixed results (for review see Kavoussi et al 340 ). Studies that compare prolactin response to fenfluramine in depressed patients before and after antidepressant treatment have yielded mixed results.…”
Section: Experimental Manipulations Of 5-ht In Relation To Sv Factorsmentioning
confidence: 99%
“…[337][338][339] Administration of D-fenfluramine results in a dosedependent rise in prolactin levels, 340 which has been used as an index of central 5-HT responsivity. [341][342][343] The prolactin response to fenfluramine in depression has been studied extensively, with mixed results (for review see Kavoussi et al 340 ). Studies that compare prolactin response to fenfluramine in depressed patients before and after antidepressant treatment have yielded mixed results.…”
Section: Experimental Manipulations Of 5-ht In Relation To Sv Factorsmentioning
confidence: 99%
“…In humans, the observation that oral administration of fenfluramine to healthy volunteers induced a dose-related increase in PRL secretion provided an index of central serotonergic function (Quattrone et al, 1983), a phenomenon that has been reliably reproduced many times over. Fenfluramine, a serotonin-releasing agent, which also inhibits the reuptake of synaptic 5-HT and stimulates postsynaptic 5-HT 2A and 2C receptors (Newman et al, 1998) induces a rapid surge of PRL in laboratory animals and humans (Lu and Meites, 1973;Pinder et al, 1975;Slater et al, 1976). In contrast to healthy controls, a blunted PRL response occurs in some depressed patients when challenged with fenfluramine (Siever et al, 1984;Cleare et al, 1995;Coccaro et al, 1989;Mann et al, 1995;O'Keane and Dinan, 1991;Lopez-Ibor et al, 1988;Mitchell and Smythe, 1990), suggesting abnormal central serotonergic transmission in this condition.…”
Section: The Ssris and Prolactinmentioning
confidence: 99%
“…However, many studies have failed to show similar results (Asnis et al, 1988;Abel et al, 1997;Maes et al, 1991;Weizman et al, 1988;Kavoussi et al, 1998). The main criticism of studies documenting a positive correlation between a blunted PRL response and depression is the use of heterogeneous patient populations with other psychiatric comorbidities (Newman et al, 1998). More recent studies indicate that blunted PRL response to fenfluramine is associated with impulsive aggression and suicidal behavior, traits associated with depression (Coccaro et al, 1989(Coccaro et al, , 1997aFava et al, 2000;New and Siever, 2002;Placidi et al, 2001).…”
Section: The Ssris and Prolactinmentioning
confidence: 99%
“…26 Neuroendocrine challenge studies with d and dl fenfluramine have consistently shown blunted release of prolactin in depressed patients and it has been reported that this blunting is a trait phenomenon which is also observed in the well state. 27 Fenfluramine-induced prolactin release has been shown to be mediated by 5-HT2C receptors. 28 The HT2CR cys23ser polymorphism examined in this study may have functional effects on mCPP binding in vitro.…”
mentioning
confidence: 99%